The addition of sirolimus to the graft‐versus‐host disease prophylaxis regimen in reduced intensity allogeneic stem cell transplantation for lymphoma: a multicentre randomized trial. (5th January 2016) - Armand, Philippe; Kim, Haesook T.; Sainvil, Marie‐Michele; Lange, Paulina B.; Giardino, Angela A.; Bachanova, Veronika; Devine, Steven M.; Waller, Edmund K.; Jagirdar, Neera; Herrera, Alex F.; Cutler, Corey; Ho, Vincent T.; et al.
Summary: Inhibition of the mechanistic target of rapamycin (mTOR) pathway has clinical activity in lymphoma. The mTOR inhibitor sirolimus has been used in the prevention and treatment of graft‐versus‐host disease (GVHD) after allogeneic haematopoietic stem cell transplantation (HSCT). A retrospective study suggested that patients with lymphoma undergoing reduced intensity conditioning (RIC) HSCT who received sirolimus as part of their GVHD prophylaxis regimen had a lower rate of relapse. We therefore performed a multicentre randomized trial comparing tacrolimus, sirolimus and methotrexate to standard regimens in adult patients undergoing RIC HSCT for lymphoma in order to assess the possible benefit of sirolimus on HSCT outcome. 139 patients were randomized. There was no difference overall in 2‐year overall survival, progression‐free survival, relapse, non‐relapse mortality or chronic GVHD. However, the sirolimus‐containing arm had a significantly lower incidence of grade II‐IV acute GVHD (9% vs. 25%, P  =   0·015), which was more marked for unrelated donor grafts. In conclusion, the addition of sirolimus for GVHD prophylaxis in RIC HSCT is associated with no increased overall toxicity and a lower risk of acute GVHD, although it does not improve survival; this regimen is an acceptable option for GVHD prevention in RIC HSCT. This trial is registered at clinicaltrials.gov (NCT00928018).